2022
DOI: 10.1111/jgh.15759
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy reduces the risk of cholangiocarcinoma in patients with complicated gallstones, but has negligible effect on hepatocellular carcinoma

Abstract: Background and Aim: Gallstones have been reported to be positively associated with hepatobiliary cancers. However, risks of these cancers by cholecystectomy or in patients with complicated gallstones are controversial. We studied the effect of cholecystectomy on the risk of cholangiocarcinoma (CCA) or hepatocellular carcinoma (HCC) in patients with gallstones and subgroup of complicated gallstones. Methods: Patients with gallstone disease (n = 958 677) and age-matched and sex-matched controls (n = 9 586 770) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…After examining the full text of these 33 potentially eligible studies, 13 studies were excluded because of the following reasons: no outcome of interest was reported ( n =3), the risk of cancer was shown with a standardized incidence ratio (SIR) instead of OR, HR, or RR ( n =4), or study populations overlapped ( n =6). Finally, 20 studies 17 36 were included in the meta-analysis consisting of 13 cohort studies 17 20 , 22 , 24 26 , 28 , 29 , 32 , 33 , 36 , 3 matched case–control studies 30 , 31 , 34 , and 4 cross-section studies 21 , 23 , 27 , 35 . The results of the literature research and study selection are detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After examining the full text of these 33 potentially eligible studies, 13 studies were excluded because of the following reasons: no outcome of interest was reported ( n =3), the risk of cancer was shown with a standardized incidence ratio (SIR) instead of OR, HR, or RR ( n =4), or study populations overlapped ( n =6). Finally, 20 studies 17 36 were included in the meta-analysis consisting of 13 cohort studies 17 20 , 22 , 24 26 , 28 , 29 , 32 , 33 , 36 , 3 matched case–control studies 30 , 31 , 34 , and 4 cross-section studies 21 , 23 , 27 , 35 . The results of the literature research and study selection are detailed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Half of the studies included in this meta-analysis were conducted in Asia ( n = 10), whereas 8 studies were carried out in the United States, and two studies were carried out in Europe. Of the 20 studies, 7 studies 18 , 21 24 , 27 , 33 evaluated the association between cholecystectomy and NAFLD, 3 studies evaluated cirrhosis 26 , 29 , 35 , and 11 studies 17 , 19 , 20 , 25 , 28 32 , 34 , 36 evaluated PLC [3 studies 17 , 29 , 30 evaluated the hepatocellular carcinoma (HCC), 3 studies 17 , 31 , 34 evaluated the intrahepatic cholangiocarcinoma (ICC), and 6 studies 19 , 20 , 25 , 28 , 32 , 36 did not distinguish HCC and ICC]. The majority of studies 17 20 , 22 , 24 26 , 28 34 , 36 included in this meta-analysis were of high quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systemic review [ 41 ] showed that CCY was associated with a significant 54% increase in the risk of cholangiocarcinoma, especially in the ECC, in comparison with healthy controls. The updated study, which focused on complicated gallstone disease patients, showed that CCY slightly decreased cholangiocarcinoma risk [ 42 ], but this study still used age-matched and sex-matched controls without further detailed confounding factors adjustments. The problems of heterogenous disease severity and inflammatory conditions due to cholelithiasis in the CCY group and in the pure gallstone disease group/normal population existed in almost all previous articles.…”
Section: Discussionmentioning
confidence: 99%